2014
DOI: 10.1016/j.fitote.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citrus bergamia juice on human neuroblastoma cells in vitro and in metastatic xenograft models

Abstract: Neuroblastoma is the most common extracranial pediatric solid tumor with poor prognosis in children with disseminated stage of disease. A number of studies show that molecules largely distributed in commonly consumed fruits and vegetables may have anti-tumor activity. In this study we evaluate the effect of Citrus bergamia (bergamot) juice (BJ) in vitro and in a spontaneous metastatic neuroblastoma SCID mouse model. Qualitative and quantitative characterizations of BJ flavonoid fractions were performed by RP-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 35 publications
1
52
0
2
Order By: Relevance
“…Cytotoxic effects of Citrus sinensis essential oil were demonstrated by MTT assay in a study with SW480 and HT-29 cells in different times of incubation (Chidambara-Murthy et al, 2012). Similarly, the incubation of LAN-1 and SK-N-SH cells with growing concentrations of Citrus bergamia juice ranging from 0.5 to 10% for 24, 48 and 72h reduced cell proliferation in a concentrationdependent manner (Navarra et al, 2014). Thus, based on our data, our results demonstrated to be safe and gave us support to continue with behavioral tests.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Cytotoxic effects of Citrus sinensis essential oil were demonstrated by MTT assay in a study with SW480 and HT-29 cells in different times of incubation (Chidambara-Murthy et al, 2012). Similarly, the incubation of LAN-1 and SK-N-SH cells with growing concentrations of Citrus bergamia juice ranging from 0.5 to 10% for 24, 48 and 72h reduced cell proliferation in a concentrationdependent manner (Navarra et al, 2014). Thus, based on our data, our results demonstrated to be safe and gave us support to continue with behavioral tests.…”
Section: Discussionsupporting
confidence: 70%
“…Thereby, development of new anxiolytics that do not induce sedative effects and/or inhibit locomotion would be highly useful (Park et al, 2005). Hence, CLEO might serve as an appealing alternative therapeutic target, because the behavior analyzed in the animals is suggestive of anxiolyticlike effect with no motor impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a clinical research showed that the bergamot-derived polyphenolic fraction, given orally in patients suffering from metabolic syndrome, produces significant reduction of serum cholesterol, triglycerides and glycaemia [28], strengthen the finding obtained in animal model. More recently, we demonstrated that BJ is also able to inhibit important molecular pathways related to cancer-associated aggressive phenotype, thus reducing growth, adhesion and migration in different in vitro [29] and in vivo models [30]. Finally, studies performed on colorectal cancer cell line verified that the antiproliferative effect of BJ is due to its flavonoid fraction which is able to act by multiple mechanisms depending on the concentration [31].…”
Section: Introductionmentioning
confidence: 81%
“…However, bergamot juice, obtained from the endocarp after essential oils extraction, has long time been considered just a secondary and discarded product of the essential oil industry due to its bitter taste. Recently, it gained attention because of its hypolipemic and hypoglycaemic activity (Mollace et al, 2011), as well as its anti-inflammatory (Impellizzeri et al, 2014; Risitano et al, 2014) and anti-cancer properties (Delle Monache et al, 2013; Navarra et al, 2014; Visalli et al, 2014). …”
Section: Introductionmentioning
confidence: 99%